IMPLEMENTATION OF "MILITARY COMMUNISM POLICY" IN TURKESTAN REGION (Western European Journal of Historical Events and Social Science, 2025)
This article shows that the "Military Communism" policy introduced by Soviet Russia in 1918-1921 emerged as a unique system of country management during the civil war. This policy was also implemented in the Turkestan region and had a profound impact on the socio-economic life of the region. Its essence was as follows. All industrial production was concentrated in the hands of the state and managed on the basis of strict centralization; farmers handed over the surplus of their own produce to the state (food distribution, i.e. distribution); and the state took over the distribution of food and industrial products; the market disappeared and money circulation was replaced by kind (products); all able-bodied population was recruited into forced labor (militarization of labor)